2020
DOI: 10.1177/0954407020964004
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic dynamics of misfires and partial burns in a dilute spark-ignition engine

Abstract: This study investigates the cyclic dynamics of cumulative heat release data past the edge of stability in a dilute spark-ignition engine. Emphasis is placed on analyzing the cyclic dynamics near the dilute limit where partial burns and misfires are frequent. These events are often followed by a higher-energy cycle due to the feed-forward mechanism present in the residual gases. These patterns are deterministic and increase the coefficient of variation to undesirable levels. Symbol sequence analysis was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Data was partitioned using the energy-basis method that was outlined in Stiffler et al 11 to allow for different cutoffs to be compared directly, but with the binning cutoffs being those shown in Table 2. Cycles with nominal heat release had a combustion efficiency around 80%–90% since heat transfer and crevice effects were neglected in the heat release calculation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Data was partitioned using the energy-basis method that was outlined in Stiffler et al 11 to allow for different cutoffs to be compared directly, but with the binning cutoffs being those shown in Table 2. Cycles with nominal heat release had a combustion efficiency around 80%–90% since heat transfer and crevice effects were neglected in the heat release calculation.…”
Section: Discussionmentioning
confidence: 99%
“…The process of symbol sequencing has been discussed earlier in this paper and full details and uses in engine studies can be found in the literature. 11,1315 Symbol sequencing only uses frequency to compare different sequences, the benefit of using additional measures available when using association rules is discussed in this section.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Moreover, the fundamental characteristics of combustion CCV can change depending on engine speed, load, and phasing. [45][46][47] Since SI engines operate over a wide range of speeds and loads, complete characterization of the dilute limit over the entire operating regime requires a large amount of time and effort. To reduce the testing burden, the Advanced Combustion and Emission Control (ACEC) tech team of the United States Council for Automotive Research (USCAR) has chosen a relevant engine speed and load condition for different technology applications.…”
Section: Dilute Limit In Spark-ignition Enginesmentioning
confidence: 99%